Marginal Gap Evaluation of Metal Onlays and Resin Nanoceramic Computer-Aided Design and Computer-Aided Manufacturing Blocks Onlays - Abdul Hamid, Nor Faharina; Wan Bakar, Wan Zaripah; Ariffin, Zaihan (European Journal of Dentistry, 2019)
Objective This study was carried out to assess and compare the marginal gap of conventionally used metal onlays and new resin nanoceramic (RNC) (Lava Ultimate block) onlays.Materials and Methods This is an in vitro study using two extracted sound human mandibular molars. One tooth was prepared to receive the metal onlays and another one for the RNC onlays which were fabricated using the computer-aided design and computer-aided manufacturing (CAD/CAM) technology. Twelve metals and 12 ceramic onlays were fabricated before they were placed at their respective preparation and examined under the Leica stereomicroscope, M125C (Leica Microsystems, Wetzlar, Germany) for a marginal analysis. The gap width was measured at 10 predefined landmarks which included 3 points on the buccal and lingual surfaces each and 2 points each on the mesial and distal surfaces, respectively.Statistical Analysis Mann–Whitney post hoc test was used for statistical analysis (P ≤ 0.05).Results Overall, the RNC onlays showed significant lower marginal gap with the exception of the landmarks 5 and 6 (on distolingual) and no significant difference at landmark 7 (on midlingual). It was observed that the marginal gap were all within the clinically acceptable limit of 120 μm.Conclusions Based on the results obtained, it can be concluded that the RNC CAD/CAM onlays are a promising alternative to the metal onlays.
Keywords: ceramics; computer-aided design; microleakage; minimally invasive dentistry; prosthetic dentistry/prosthodontics; restorative materials